2011
DOI: 10.1016/j.contraception.2011.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Medical vs. surgical abortion: the importance of women's choice

Abstract: Background Using a large national sample of women undergoing an abortion in France, we explore the factors associated with medical or surgical abortion. We draw particular attention to the influence of women’s preferences in the decision making process. Study design The data are drawn from a nationally representative survey of 8,245 women undergoing an elective abortion in France in 2007. Analyses of factors associated with the type of abortion technique were performed among the 4,650 women who were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 13 publications
0
16
1
Order By: Relevance
“…Results of a study conducted in Ethiopia also found that the proportion of women who would choose the same method again if needed after having medical abortion was higher than that in women who had undergone surgical abortion (83.3% vs 77.4%), and the proportion of women who would recommend the same method to their friends after having medical abortion was also higher than that in women who had undergone surgical abortion (94.0% vs 86.8%) 20 . In contrast with women's preference for medical abortion in previous studies, 17,20 in the present study, among providers who had a preference in abortion methods, the proportion of providers with preference for surgical abortion was more than double that of those with preference for medical abortion (69.8% vs 30.2%). The preference discrepancy between providers and women seeking abortion might be due to finance.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Results of a study conducted in Ethiopia also found that the proportion of women who would choose the same method again if needed after having medical abortion was higher than that in women who had undergone surgical abortion (83.3% vs 77.4%), and the proportion of women who would recommend the same method to their friends after having medical abortion was also higher than that in women who had undergone surgical abortion (94.0% vs 86.8%) 20 . In contrast with women's preference for medical abortion in previous studies, 17,20 in the present study, among providers who had a preference in abortion methods, the proportion of providers with preference for surgical abortion was more than double that of those with preference for medical abortion (69.8% vs 30.2%). The preference discrepancy between providers and women seeking abortion might be due to finance.…”
Section: Discussioncontrasting
confidence: 87%
“…Consequently, medical abortion was becoming more and more popular among women seeking abortion. In a national representative survey including 8245 women undergoing abortion in France, the proportion of women who underwent a medical procedure among those given elective abortion was much higher than those not given a choice (84% vs 52%) 17 . A study of 414 subjects with gestation up to 63 days in northwest Ethiopia indicated that women undergoing medical abortion were more satisfied than those undergoing surgical abortion (91.2% vs 82.4%) 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While safe surgical services are becoming more widespread, there is still a risk of complications, such as uterine adhesion, from these procedures. In addition, as seen in the induced abortion literature, many women prefer medical over surgical treatment when given the option [12-14]. Introducing misoprostol treatment for incomplete abortion is an important step towards improving care for women experiencing abortion complications.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment can be taken earlier in pregnancy, and women can safely undergo the abortion at home, and experience it more naturally as a miscarriage, 10 options that women value and find acceptable. 11 Recent data from England, Wales and France indicate that amongst women eligible for both options, a majority chose medical, 12,13 and in the United States, this proportion is steadily increasing. 14 In Australia, the number of certified prescribers and pharmacy dispensers is growing, including in non-metropolitan areas.…”
mentioning
confidence: 99%